Review study on empathy is virtuous in the practice of medicine - Vidya, Bhagat; Nordin, Simbak; Sheila, Menon (2019)
Empathy is a behavioral virtue, which can enhance the practice of medicine. At the same time it is identified that not all physicians are empathic in their communication with patients. This study focuses on the benefits of empathetic communication and the impact of the observable decline in physicians’ who are genuinely empathic towards patients. The aim of this study is to present an argument for empathy as a behavioral virtue within the practice of medicine. This literature review was completed using electronic databases. The study had analyzed 40 articles from the years 1986 to 2017. The reviewed articles focused on the nature and types of empathy, its significance in the medical profession, and on enhancing natural empathic ability. The current study concludes that empathy is a part of human nature which can be measured and nurtured although the process it not an easy one. The current study suggests that research in the area can lead to better training programs for medical professionals.